2007
DOI: 10.1111/j.1365-2934.2007.00761.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a new model of care for patients with chronic musculoskeletal pain

Abstract: The nurse consultant's role was pivotal in the implementation of the chronic pain service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Similarly, the exchange, gathering and sharing of implicit, explicit and cultural knowledge within the teams increased. This is significant since the utilization of expertise is important in the development of nursing [6,16,25,26] as the combined knowledge, skills of co-operating team members inevitably exceeds their individual knowledge and skills. In addition to processing information, the participants indicated that multiprofessional learning, responsibility and commitment were central to good teamwork, again in accordance with previous findings [8,11,12,19] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the exchange, gathering and sharing of implicit, explicit and cultural knowledge within the teams increased. This is significant since the utilization of expertise is important in the development of nursing [6,16,25,26] as the combined knowledge, skills of co-operating team members inevitably exceeds their individual knowledge and skills. In addition to processing information, the participants indicated that multiprofessional learning, responsibility and commitment were central to good teamwork, again in accordance with previous findings [8,11,12,19] .…”
Section: Resultsmentioning
confidence: 99%
“…Successful patient education requires seamless co-operation between healthcare units throughout the whole service process, and the employment of similar educational practices by all nursing staff within a given healthcare network [4,5] . The continuity of treatment for patients with long-term illnesses is promoted including by patient-based operation, flawless information flow, well-founded treatment programs and recommendations as well as multidisciplinary co-operation and staff training [3,6] . Hence, evaluating care pathways, developing operation models, strengthening healthcare personnel's education skills, and enhancing co-operation between primary and special healthcare units, are all important aspects of development in the field of healthcare [5,7,9,15] .…”
Section: Introductionmentioning
confidence: 99%
“…59 They may be responsible for the patient from admission to discharge, 80 without the patient seeing a doctor. 77 In other cases, nurses were in charge of the development and implementation of a specific specialist service, such as a chronic musculoskeletal pain service 42 or a mental health liaison service. 81 Steers et al, 82 based on a review of the evidence of providing palliative care in community hospitals in the UK, concluded that GPs generally acknowledged their dependence on nursing staff to support them to make timely management decisions following the admission of patients.…”
Section: The Role Of Nursesmentioning
confidence: 99%
“…Examples include a treatment and diagnostic centre for gynaecology, 64 and a nurse-consultant-led clinic for patients with chronic musculoskeletal pain, 42 both set in the UK. Several studies reported on outpatient services that were developed in collaboration with larger hospitals, such as services for people with eating disorders, which used videoconferencing to connect participants in community hospital sites and a specialist service within a large urban hospital for weekly therapy sessions.…”
Section: Community Hospitals In Selected High-income Countries: a Scomentioning
confidence: 99%
See 1 more Smart Citation